Development Of A Web Based Final Project Monitoring Information System In The Faculty Of Science And Technology UIN Sumatera Utara - Mutia, Mutia; Alda, Muhamad (UIN Sumatera Utara Medan, 2024)
The management of the final project at the Faculty of Science and Technology, State Islamic University of North Sumatra has not been fully supported by an application system. The head of the study program faces difficulties in preparing the final project management report, which has an impact on the less than optimal process of monitoring the final project by students and supervisors. Supervisors experience limitations in monitoring the development of their students optimally, especially because of the large number of students and the variety of problems that arise. The consultation function becomes less effective. In addition, the delivery of information related to the final project to students, lecturers, and the head of the study program is often hampered, while physical files are vulnerable to being tucked away or manipulated. Students also have to come directly to campus to take the supervisor's assignment letter, submit documents, follow the guidance, and check the seminar and trial schedule. To overcome this problem, this research aims to build a web-based final project monitoring information system at the Faculty of Science and Technology, State Islamic University of North Sumatra. The research was conducted using the Research and Development (R&D) method with a Waterfall system development approach. The result of this research is a web-based SIMTA (Final Project Monitoring Information System) developed using the Laravel framework. SIMTA is expected to facilitate the process of completing the final project, increase the effectiveness and efficiency of interaction between students, lecturers, and study programs.